The Regulatory Role of Work Engagement in the Relationship Between Work Values and Affective Organizational Commitment of Generation Y Production Workers in Industry - Ümit Deniz İlhan; Burcu Kümbül Güler; Mehmet Aksaraylı (Journal of Economy Culture and Society)
This study focuses on the effects of work engagement and work values that are thought to be effective in providing the affective organizational commitment of Generation Y production workers in industry within the framework of the changes in working life. The data of the research were collected from a total of 516 Generation Y production workers (women %12,8, men %87,2) in two large-scale enterprises operating in the field of food and beverage production in the province of İzmir, Turkey. Work values were assessed through Lyons, Higgins, Chris and Duxbury’s (2010) Lyons Work Values Survey (LWVS). Next, to assess work engagement, Utrecht Work Engagement Scale (UWES) developed by Schaufeli, Salanova, González-Romá and Bakker (2002) was used. Last, 6 items of Meyer and Allen’s (1991) Organizational Commitment Questionnaire (OCQ) related to affective commitment were used to assess affective organizational commitment. According to the results of the study, work engagement was found to have a regulatory role in three out of four dimensions of work values (intrinsic-present oriented, extrinsic-present oriented, and extrinsic-future oriented, with intrinsicfuture oriented not found) and affective organizational commitment. In line with these findings, to ensure the affective organizational commitment of Generation Y production workers in industry, it is suggested to create an organizational environment that enables work engagement while giving importance to work values.